A study on the importance of personal accident towards motor insurance / Amir Fauzi Abd Aziz and Nur Aziana Said Askar Ali - Abd Aziz, Amir Fauzi; Said Askar Ali, Nur Aziana (Faculty of Business and Management, 2013)
Personal Accident insurance is the cheapest and smartest way of filling the insurance gap especially for driver who are aware of the importance of personal accident coverage to their self and the passenger. By adding Personal accident insurance into car insurance policy, it will be able to secure a one off monetary payment for driver and passengers who suffered physical harm, permanently injured or killed in a serious road accident involving a car. The research is conducted to study a factors that make Personal Accident Insurance is importance in relation to road accident injuries. This is because nowadays, many road accidents involve with serious body injury to driver and passenger. The intent of personal accident insurance is to protect participant injury whilst they are involved in road activities. The objective of the study is 1) to identify the importance of personal accident towards motor insurance. 2) to identify the major factors that can make the personal accident is importance towards motor insurance. 100 respondents consist of road users at Johor Bahru, Johor become the sample study. The researchers suggests three factors that can make personal accident insurance is important towards motor insurance and the finding shows that weather affect to personal accident. Suggestion and recommendation is including to people know the others factors that relate with the personal accident in future.